Cry for Luck : Sacred Song and Speech among the Yurok, Hupa, and Karok Indians of Northwestern California. - Keeling, Richard (UC Press voices revived., 2022)
The ""sobbing"" vocal quality in many traditional songs of northwestern California Indian tribes inspired the title of Richard Keeling's comprehensive study. Little has been known about the music of aboriginal Californians, and Cry for Luck will be welcomed by those who see the interpretation of music as a key to understanding other aspects of Native American religion and culture. Among the Yurok, Hupa, and Karok peoples, medicine songs and spoken formulas wer.